1991
DOI: 10.1002/ajmg.1320380425
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological aspects of Mendelian syndromes in a Spanish population sample: II. Autosomal recessive malformation syndromes

Abstract: From April, 1976, to December, 1988, the Spanish Collaborative Study of Congenital Malformations (ECEMC) monitored a total population of 710,815 liveborn infants in 16 of 17 Spanish Regions and identified 14,439 (2.0%) with congenital defects. Among the malformed children, we identified 73 with well recognized autosomal recessive syndromes, for an overall prevalence rate of 10.3 per 100,000 livebirths and a total carrier frequency of 1/49. Considering the Spanish Regions (Comunidades Autónomas), we analyzed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Infantile PKD is an autosomal recessive malformation syndrome caused by mutations in PKHD1 . PKD is one of the more common of autosomal recessive congenital malformation syndromes (Martinez‐Frias et al,1991). The birth prevalence in Texas was within the reported estimates ranging from 1.41/100,000 (Martinez‐Frias et al,1991) to 12.6/100,000 (Kääriäinen,1987).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infantile PKD is an autosomal recessive malformation syndrome caused by mutations in PKHD1 . PKD is one of the more common of autosomal recessive congenital malformation syndromes (Martinez‐Frias et al,1991). The birth prevalence in Texas was within the reported estimates ranging from 1.41/100,000 (Martinez‐Frias et al,1991) to 12.6/100,000 (Kääriäinen,1987).…”
Section: Discussionmentioning
confidence: 99%
“…PKD is one of the more common of autosomal recessive congenital malformation syndromes (Martinez‐Frias et al,1991). The birth prevalence in Texas was within the reported estimates ranging from 1.41/100,000 (Martinez‐Frias et al,1991) to 12.6/100,000 (Kääriäinen,1987). Our findings for the infant gender rates were consistent with the literature's gender ratio of 1:1 (Kääriäinen,1987).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the population incidence of sporadic cases (10,(18)(19)(20)38), both conditions have exceptionally high mutation frequencies (1͞15,000-1͞70,000) when compared with what is known about other single nucleotide substitutions at CpG sites (40). This high rate led to the original idea of a DNA mutation hot spot (14,15,37,41).…”
Section: Discussionmentioning
confidence: 99%
“…Second, all sporadic achondroplasia cases have been found to inherit the G1138A mutation from their father (17). Third, recent data on the population incidence of sporadic achondroplasia (10,(18)(19)(20) predict the average frequency of sperm carrying the mutation in normal individuals will be in a range detectable by modern molecular methods (1͞15,000 to 1͞70,000). Our studies on sperm DNA from men of different ages suggest that the observed increase in G1138A mutation frequency cannot satisfactorily explain the exponential increase in sporadic achondroplasia cases with paternal age.…”
mentioning
confidence: 99%
“…Our hypothesis of a mutator gene may fit well with these premutagenic lesions. Moreover achondroplasia has exceptionally high mutation frequencies (1/15,000–1/70,000) [Camera and Mastroiacovo, 1988; Stoll et al, 1989; Martinez Frias et al, 1991; Orioli et al, 1995; Wilkie et al, 1995] when compared with the mutation frequencies of other single nucleotides substitutions at CpG sites [Nachman and Crowell, 2000].…”
Section: Discussionmentioning
confidence: 99%